Marketing a new route : Norwegian flies London-Singapore - O'Brien, Justin (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Dominic Tucker, Head of United Kingdom and Ireland Sales for low-cost, high-quality airline Norwegian, has to decide how best to develop his extended sales territory, in far-away Singapore. With limited data and a small marketing budget, he has to assess the long-term potential of the market before considering his tactics; what would the optimal local sales representation look like and would social influencers play a useful role? This case encourages students to appreciate some realistic sales promotion and marketing challenges faced by a new market entrant, including market and route development, airline economics, competitive pricing strategies, and leveraging low cost promotion.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Norwegian Air Shuttle (Airline); Airlines -- Norway -- Case studies; Aeronautics, Commerical -- Norway -- Case studies